ANALISIS PENGARUH PRICE EARNINGS RATIO (P/E) DAN MARKET TO BOOK RATIO (P/B) TERHADAP PERTUMBUHAN EARNINGS (GROWTH) PERUSAHAAN MANUFAKTUR DI INDONESIA - Halim Dedy Perdana (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2006)
ABSTRACT The objective of this research is to examine the analysis influence of Price Earnings Ratio (P/E) and Market to Book Ratio (P/B) to growth that residual earnings as proxy of manufacturer companies that listed in Jakarta Stock Exchange from 1999 – 2003. The sample was taken by using purposive sampling method and based on the criterion stated before; the samples collected were 41 companies. The result of this research shows that in partial evaluation model between Price Earnings Ratio (P/E) and Market to Book Ratio (P/B) as independent variable to growth only significant in one period (P/B in 1999). For jointly evaluation model between Price Earnings Ratio (P/E) and Market to Book Ratio (P/B) to growth significant on 1999 and 2000. The other result of this research shows that Price Earnings Ratio (P/E) wasn’t sufficient indicator to evaluate growth because significant if used to jointly evaluation with other variable (Market to Book Ratio), whereas P/B was sufficient indicator to evaluate growth. Jointly, Price Earnings Ratio (P/E) and Market to Book Ratio (P/B) can be used to evaluate growth for partial time. Keywords: Price Earnings Ratio,  Market to Book Ratio, Growth